Review paperPostconditioning: a brief review - Schipke, Jochen D.; Halkos, Michael E.; Kerendi, Faraz; Gams, Emmeran; Vinten-Johansen, Jacob (Archives of Medical Science, 2006)
Preconditioning represents the most effective form of cardioprotection that can be induced to attenuate the injury accompanying a longer lasting ischemia (=index ischemia) of sufficient duration and severity to cause myocardial necrosis. Preconditioning can be induced by short bouts of ischemia, several pharmaceuticals (e.g. adenosine), and volatile anesthetics all imposed before the index ischemia. A brief ischemia of an organ other than the heart can likewise initiate protection of the heart, which has been called “preconditioning at a distance” or “remote preconditioning”. According to the more recent literature, short bouts of ischemia after an index ischemia can also initiate cardioprotection, e.g. improved post-ischemic endothelial function, reduced infarct size and less apoptosis; this protective maneuver has been called “postconditioning”. Postconditioning can also be elicited at a distant organ, termed “remote postconditioning”. It is the aim of this short review to (1) characterize preconditioning and in particular postconditioning, (2) describe possible mechanisms, and (3) call attention to the clinical relevance of this cardioprotective strategy.